Management of Endodontic Patient Associated with Sodium Hypochlorite Accident in Chaiyaphum Hospital: a Case Report - Pummark, Siriporn (Journal of Health Science of Thailand, 2017)
A 13-year-old healthy boy was undergoing routine endodontic therapy at Chaiyaphum hospital. During irrigation of root canal treatment of a right maxillary central incisor (#11), 5.0% sodium hypochlorite was forced through the apical foramen. The patient experienced acute severe pain attack in the right maxillary region accompanied by an increasing edema and hematoma of his upper lip, buccal region and suborbital area. This accident led to hemolysis, hematuria, and bleeding tendency, the sudden rise of PT more than 120 seconds and INR 9.8, two hours later. He was consulted urgently to the emergency room. He was given fresh frozen plasma and high dose of antibiotic for secondary infection. He recovered from hematuria and bleeding tendency after 5 and 10 days of hospitalization, respectively. His swelling resolved in 10 weeks, later. The tooth was completed root canal treatment. The patient got both physical and mental care. The good relation between patient, parents and the hospital had been restored. The management of this complication was discussed. However, there had never been such a report of hypochlorite accident in Thailand. This report reveals that sodium hypochlorite must be used carefully during root canal treatment.